2017
DOI: 10.3389/fcell.2017.00028
|View full text |Cite
|
Sign up to set email alerts
|

TGF-β1 Pretreatment Improves the Function of Mesenchymal Stem Cells in the Wound Bed

Abstract: The wound healing process initiates after injury to a tissue and involves a series of orchestrated events to minimize the invasion of foreign matters such as bacteria and efficiently regenerate the damaged tissue. A variety of cells must be recruited to the tissue during wound healing. However, this process is severely disrupted in patients suffering from chronic illness, including diabetes, leading to impaired healing or non-healing wounds. Current avenues of treatment include negative-pressure therapy, wound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 84 publications
1
17
0
Order By: Relevance
“…TGF-β1 also plays an important role in directing fate decision in B-MSCs and modulating regenerative function of B-MSCs [ 26 28 ]. We analyzed the response to TGF-β1 stimulation on control and IPF B-MSCs at 24 h and 72 h. At 24 h, IPF-MSCs expressed higher levels of interleukin (IL)-6 (a well-known factor of SASP) than control cells (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…TGF-β1 also plays an important role in directing fate decision in B-MSCs and modulating regenerative function of B-MSCs [ 26 28 ]. We analyzed the response to TGF-β1 stimulation on control and IPF B-MSCs at 24 h and 72 h. At 24 h, IPF-MSCs expressed higher levels of interleukin (IL)-6 (a well-known factor of SASP) than control cells (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…Platelet release of TGF-β and extracellular matrix (ECM) tension, help drive fibroblasts to transition into a myofibroblast phenotype that help with repair [180,181]. It also enhances mesenchymal stem cells (MSCs) differentiation and functions as a mechano-stimulatory factor to improve wound closure [182]. Platelet TGF-β also helps neutrophils infiltrate into wounds that are replaced by macrophages.…”
Section: Platelet Mediated Thrombogenesis Inflammatory and Resolutimentioning
confidence: 99%
“…5) ). It has been previously demonstrated that MSCs increase the rate of wound closure in full thickness skin wounds (Ghosh et al, 2017[ 11 ]). Moreover, MSCs promote skin appendages regeneration (Xia et al, 2017[ 37 ]).…”
Section: Discussionmentioning
confidence: 99%